1996
DOI: 10.1080/01688639608408313
|View full text |Cite
|
Sign up to set email alerts
|

Victoria symptom validity test: Efficiency for detecting feigned memory impairment and relationship to neuropsychological tests and MMPI-2 validity scales

Abstract: Error scores and response times from a computer-administered, forced-choice recognition test of symptom validity were evaluated for efficiency in detecting feigned memory deficits. Participants included controls (n = 95), experimental malingerers (n = 43), compensation-seeking patients (n = 206), and patients not seeking financial compensation (n = 32). Adopting a three-level cut-score system that classified participant performance as malingered, questionable, or valid greatly improved sensitivity with relativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
84
0
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 167 publications
(88 citation statements)
references
References 27 publications
3
84
0
1
Order By: Relevance
“…The VSVT is a Windows-based computerized task that has been used to classify malingerers of memory deficits, questionable malingerers, or valid test-takers with a high degree of sensitivity, 82 and cut-off scores have been developed for this purpose. 83 Computerized assessments using the VSVT yielded unique intraindividual variability data that helped differentiate among those feigning symptoms related to head trauma and those performing their best, and the response inconsistency across testing sessions is believed to be a clinically useful measure for the detection of malingering.…”
Section: Symptom Validity Testingmentioning
confidence: 99%
“…The VSVT is a Windows-based computerized task that has been used to classify malingerers of memory deficits, questionable malingerers, or valid test-takers with a high degree of sensitivity, 82 and cut-off scores have been developed for this purpose. 83 Computerized assessments using the VSVT yielded unique intraindividual variability data that helped differentiate among those feigning symptoms related to head trauma and those performing their best, and the response inconsistency across testing sessions is believed to be a clinically useful measure for the detection of malingering.…”
Section: Symptom Validity Testingmentioning
confidence: 99%
“…Thus, by exerting inadequate or suboptimal effort, feigners often perform more poorly than individuals with genuine cognitive impairment. Examples of these instruments include the Test of Memory Malingering (TOMM; Tombaugh, 1996), the Victoria Symptom Validity Test (VSVT; Slick, Hopp, Strauss, & Thompson, 2005), and the Word Memory Test (WMT; Green, Allen, & Astner, 1996).…”
mentioning
confidence: 99%
“…In addition to the MMPI-2, all respondents completed a variety of neuropsychological measures as part of their comprehensive evaluation, and forcedchoice effort measures. Effort tests included the Victoria Symptom Validity Test (VSVT; Slick et al, 1995), the Test of Memory Malingering (TOMM; Tombaugh, 1996), the Multi-Digit Memory Test (MDMT; Niccolls & Bolter, 1991), the Word Memory Test (WMT; Green, 2003), and the Letter Memory Test (LMT; Inman et al, 1998).…”
Section: Methodsmentioning
confidence: 99%
“…A previous meta-analysis (Vickery et al, 2001) found the Digit Memory Test (DMT; Hiscock & Hiscock, 1989) to be most effective in identifying IE relative to other effort measures examined, including non-forced-choice measures. Similar forced-choice measures, such as the Victoria Symptom Validity Test (VSVT; Slick et al, 1995), the Test of Memory Malingering (TOMM; Tombaugh, 1996), Multi-Digit Memory Test (MDMT; Niccolls & Bolter, 1991), Word Memory Test (WMT; Green, 2003), and the Letter Memory Test (LMT; Inman et al, 1998) have also demonstrated respective utility in civil and simulating samples.…”
Section: Introductionmentioning
confidence: 99%